Demystifying the "Triple Point: " Technical Nuances of the Fronto-Orbital Advancement. Issue 3 (May 2018) - Lopez, Christopher D.; Kumar, Anand; Lin, Alexander Y.; Bonfield, Christopher M.; Weinzweig, Jeffrey; Naidich, Thomas; Smith, Christopher M.; Taub, Peter J.
Abstract : Abstract: Removal of the fronto-orbital bandeau is one of the most critical components for procedures designed to correct anomalies of the craniofacial skeleton and remodel the anterior calvarial vault. It is also used to improve exposure of the anterior cranial fossa. It is arguably one of the more difficult portions of some craniofacial procedures. While the technique for fronto-orbito-sphenoid osteotomy has been frequently described, it has only been minimally detailed. Separation of bone in this region remains challenging due to the bone thickness, adjacent vital structures, and limited direct visibility. The present paper describes the anatomy of this particular region, which the authors have termed the "triple point", to facilitate successful osteotomy and avoid potential injury.